Proceedings of the 16th International Symposium on Management (INSYMA 2019) 2019
DOI: 10.2991/insyma-19.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization, firm performance, and capital structure: an empirical study in Indonesia

Abstract: The objective of this study is to examine the impact of internationalization, firm perfo rmance, and capital structure: an empirical study in Indonesia. This research used industrial manufacturing companies listed on the Indonesian Stock Exchange over the 2012 -2016 period. The dependent variable in this study is the capital structure. Independent variables used are internationalization an d firm performance, Control variables used are size, age current ratio, tangibility, and total asset turn over. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Exports are expected to increase the achievement of firm performance. From research conducted in Indonesia on the manufacturing industry listed on the Indonesia Stock Exchange from 2012 to 2016, exports had a significant positive impact on firm performance based on the achievement of the firm's historical targets [45]. However, other studies have found the negative effect of exports on firm performance due to the costs of internationalization that arise [46].…”
Section: Increasing Firm Performance Through Interfirm Network and Ex...mentioning
confidence: 99%
“…Exports are expected to increase the achievement of firm performance. From research conducted in Indonesia on the manufacturing industry listed on the Indonesia Stock Exchange from 2012 to 2016, exports had a significant positive impact on firm performance based on the achievement of the firm's historical targets [45]. However, other studies have found the negative effect of exports on firm performance due to the costs of internationalization that arise [46].…”
Section: Increasing Firm Performance Through Interfirm Network and Ex...mentioning
confidence: 99%
“…To solve the bias problems that may be caused by the omission of variables in the equation of the model, as much as possible, this study controls the effects of these variables. Ten control variables are selected: stock returns (Ret) (Wang G et al, 2021), liquid ratio (Lr) (Zhang et al, 2015), enterprise total profit growth ratio (Np) (Huo and Zhang, 2017), enterprise age (Age) (Carnahan et al, 2010), enterprise liabilities to assets (L/A) ratio (Lev) (Díaz-Fernández et al, 2015), enterprise total asset turnover ratio (Tato) (Edward and Marciano, 2019), the enterprise growth rate of net profit (Profit) (Gao et al, 2021), enterprise operating growth ratio (Revenue) (Fu and Shen, 2020), equity nature (State) (Li, 2011), and Tobin's q (Tq) (Lee et al, 2021) as control variables, and selects assets scale (Size) (Goll et al, 2008) and return on equity (Roe) (He et al, 2020) as replacement variables for the robustness test. Ret, Lr, Np, Lev, Tato, Profit, Revenue, Tq, Roe are collected from the financial annual reports of the enterprises.…”
Section: Control Variablesmentioning
confidence: 99%
“…The enterprise age is measured as the reporting period minus the number of years that the enterprise has been in the market (measured in months). Younger enterprises tend to be aggressive and innovative, while older enterprises usually experience organizational rigidity and reduced efficiency (Loderer and Waelchli, 2011;Edward and Marciano, 2019). Thus, enterprise age may affect financial performance by influencing the strategic decisions of the enterprise.…”
Section: Control Variablesmentioning
confidence: 99%